2020
DOI: 10.3390/microorganisms8050626
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides from Rat-Tailed Maggots of the Drone Fly Eristalis tenax Show Potent Activity against Multidrug-Resistant Gram-Negative Bacteria

Abstract: The spread of multidrug-resistant Gram-negative bacteria is an increasing threat to human health, because novel compound classes for the development of antibiotics have not been discovered for decades. Antimicrobial peptides (AMPs) may provide a much-needed breakthrough because these immunity-related defense molecules protect many eukaryotes against Gram-negative pathogens. Recent concepts in evolutionary immunology predict the presence of potent AMPs in insects that have adapted to survive in habitats with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…We found that, rat-tailed maggot hemolymph with the concentration of 25-30 µg /100 µl and 35-40 µg / 100 µl, respectively are enough to kill Escherichia coli and Salmonella typhimurium, respectively. Our ndings corroborated with earlier studies, identi ed the role of normal hemolymphs to kill different kinds of bacteria (Sahalan et al, 2006;Basseri et al, 2016;Hirsch et al, 2020;Lee et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…We found that, rat-tailed maggot hemolymph with the concentration of 25-30 µg /100 µl and 35-40 µg / 100 µl, respectively are enough to kill Escherichia coli and Salmonella typhimurium, respectively. Our ndings corroborated with earlier studies, identi ed the role of normal hemolymphs to kill different kinds of bacteria (Sahalan et al, 2006;Basseri et al, 2016;Hirsch et al, 2020;Lee et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The immune system of the insect H. illucens is very developed, as this species feeds on decaying substrates and manure, which are extremely rich in pathogenic microorganisms, as it possible to observe also in other species, such as in Eristalis tenax . Twenty-two AMPs were indeed identified in the Diptera E. tenax , that has been able to adapt to different aquatic habitats (sewage tanks and manure pits) with heavy microbial load 29 . AMPs, which are synthesized by the fat body and hemocytes and then secreted into the hemolymph, are an essential part of the immune defense 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…However, vitro induction to immune transcripts in Eristalis tenax maggots was performed by and followed by Hirsch et al, (2020). identified thirty novel genes of E. tenax that were induced in response to septic injury including novel putative AMPs.…”
Section: Anddiscussion -Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…identified thirty novel genes of E. tenax that were induced in response to septic injury including novel putative AMPs. Hirsch et al, (2020) tested the antibacterial activity under simulated physiological conditions, a bacterial lipopolysaccharide was injected into Eristalis tenax maggots to enhance immunity-related AMPs that are synthesized in response to the injection, they are identified twenty-two AMPs and selected nine for larger-scale synthesis to test their activity against multidrugresistant Gram-negative bacteria. A diptericin-like peptide (EtDip) and two cecropin-like peptides (EtCec1-a and EtCec2-a) displayed strong activity against the pathogens.…”
Section: Anddiscussion -Antimicrobial Susceptibility Testingmentioning
confidence: 99%